A snap-shot assessment of carbon emission and export in a pristine river draining permafrost peatlands (Taz River, Western Siberia) - Vorobyev, Sergey N. (биолог); Pokrovsky, Oleg S.; Korets, Mikhail A.; Shirokova, Liudmila S. (Frontiers in Environmental Science, 2022)
Mobilization of dissolved organic carbon (DOC) and CO2 from the frozen peat to surface waters in the permafrost zone of high latitude regions is expected to enhance under on-going permafrost thaw and active layer thickness deepening. Here we explored one of the most remote, pristine, unregulated and yet environmentally important rivers in western Siberia (Taz). This subarctic river drains through forested and tundra peat bogs over a gradient of permafrost and climate and likely acts as an important conduit of CO2 to the atmosphere and carbon and nutrient exporter to the Arctic Ocean. In a snapshot study during end of spring flood–beginning of summer baseflow (July 2019), we monitored daytime CO2 and CH4 concentrations and measured CO2 emissions using floating chambers in the main stem (700 km from the upper reaches to the mouth) and 16 main tributaries and we also assessed day/night variations in the emissions. We further tested the impact of land cover parameters of the watershed and tributaries. Based on regular monitoring of the terminal (gauging) station, we quantified the C export to the Arctic Ocean during the study period. We revealed sizable CO2 emissions from the main stem and tributaries (1.0 ± 0.4 and 1.8 ± 0.6 g C-CO2 m−2 d−1, respectively). The CO2 concentrations positively correlated with dissolved organic carbon (DOC), whereas the CH4 concentrations could be partially controlled by dissolved nutrients (N, P) and proportion of light coniferous forest at the watershed. The overall C emission from the water surfaces (4,845 km2) of the Taz basin (150,000 km2) during open water period (6 months, May to October) was estimated as 0.92 Tg C (>99.5% C-CO2, <0.5% C-CH4) which is twice higher than the total dissolved C (organic and inorganic) riverine export flux during the same period. Applying a “substituting space for time” approach for northern and southern parts of the river basin, we suggest that the current riverine CO2 emission may increase 2 to 3 fold in the next decades due to on-going ...